PERSONAL DIMENSION OF ABAI'S PHILOSOPHICAL HERITAGE: THE IMPORTANCE OF IDEAS FOR MODERN HUMANITY - Pirniyazova Turdigul (Modern American Journals, 2025)
The article analyzes Abai Qunanbaiuly's philosophical legacy from the perspective of his spiritual and ethical development. The relevance of the research is determined by the importance of Abai's thoughts on freedom, humanity, labor, and education in modernizing the system of humanistic values in the current era of globalization. The article substantiates the role of the thinker's principles of diligence and the pursuit of knowledge in the process of social progress and personal self-improvement. As a result of the research, it is proven that Abai's philosophical views offer a universal system of values aimed at forming the moral culture of modern society and establishing free thinking and responsibility as the main qualities of personality.
Keywords: Abai Qunanbaiuly, philosophical heritage, personal dimension, freedom, humanity, labor, knowledge, concept of the complete person, spiritual development, humanism.